2019
DOI: 10.2337/db18-1237
|View full text |Cite
|
Sign up to set email alerts
|

Modified UCN2 Peptide Acts as an Insulin Sensitizer in Skeletal Muscle of Obese Mice

Abstract: The neuropeptide urocortin 2 (UCN2) and its receptor corticotropin-releasing hormone receptor 2 (CRHR2) are highly expressed in skeletal muscle and play a role in regulating energy balance and glucose metabolism. We investigated a modified UCN2 peptide as a potential therapeutic agent for the treatment of obesity and insulin resistance, with a specific focus on skeletal muscle. High-fat–fed mice (C57BL/6J) were injected daily with a PEGylated UCN2 peptide (compound A) at 0.3 mg/kg subcutaneously for 14 days. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…Akt, a pivotal signal transducer for growth and survival, can be activated at Thr-308 and Ser-473 regulatory sites [ 33 , 34 ]. Balasuriya et al found that Thr-308 phosphorylation increase Akt1’s catalytic rate 1500-fold [ 35 ], confirming that Thr-308 phosphorylation, but not Ser-473, is required for Akt activation.…”
Section: Discussionmentioning
confidence: 99%
“…Akt, a pivotal signal transducer for growth and survival, can be activated at Thr-308 and Ser-473 regulatory sites [ 33 , 34 ]. Balasuriya et al found that Thr-308 phosphorylation increase Akt1’s catalytic rate 1500-fold [ 35 ], confirming that Thr-308 phosphorylation, but not Ser-473, is required for Akt activation.…”
Section: Discussionmentioning
confidence: 99%
“…Modified human UCN2 peptides (Compounds A and B) are based on the previously reported Compound 8 26 and synthesized using established solid‐phase peptide synthesis protocols as described. 25 , 26 While Compound B corresponds to the Compound 8, Compound A has a further modification, with a cystine residue at position 29, where a polyethylene glycol (PEG) 20 000 is attached through an acetamide‐base linker. Formulated aliquots of the peptides in phosphate‐buffered saline were stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetic properties of Compound A have been described 25 and have a half‐life of 22.3 h. The pharmacokinetic properties of Compound B have been described 26 and result in a considerably shorter half‐life of ~30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations